Karakterisasi Actinomycetes yang Berasosiasi dengan Porifera (Axinella spp.) dari Perairan Pulau Lemukutan Kalimantan Barat - Biologi, Elisa Armaida, Siti Khotimah, (Jurnal Protobiont, 2016)
Actinomycetes are microbes that potential to produce various bioactive compounds that have benefit to pharmacology. Porifera is one of marine organism that associated with Actinomycetes. The research was conducted to determine the genera of Actinomycetes associated with porifera (Axinella spp.). Isolation was done by using pour plate and streak plate method on starch-casein agar (SCA). The preparation of microscopic speciments used slide culture method. The isolates were observed and identified by using characteristic of macroscopic, microscopic and biochemical test reaction. The isolation of Actinomycetes associated with porifera (Axinella spp.) was found four genera of Actinomycetes i.e. Nocardia, Micrococcus, Streptomyces and Corynebacterium.